Scalability of bidirectional vehicle strings with static and dynamic measurement errors. (December 2015) - Knorn, Steffi; Donaire, Alejandro; Agüero, Juan C.; Middleton, Richard H.
Abstract: Poor scalability arises in many vehicle platoon problems. Bidirectional strings appear to show some promise for mitigating these problems. In some cases these solutions have the undesirable side effect of non-scalable response to measurement errors. We examine this problem and show how information exchange between neighbouring vehicles may eliminate scalability difficulties due to measurement errors.